Knowledge, attitude and practices about contraception among married reproductive women - D., Tejaswini; J. C., Spandana; Bai, Sunanda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Total unmet need for contraception at national level has been 20.5% (DLHS 3, 2007-08). According to NFHS 4 (2015-16), total unmet need for family planning for Bangalore Urban is 13.3%. This study has been done to assess the knowledge, attitude and practices about contraception among married women in the reproductive age group. Methods: Cross sectional study conducted from 1st March 2017 to 15th April 2017 in Bowring and Lady Curzon Hospital, Bangalore. Married women in age group of 15 to 45 years, antenatal women were included. Unmarried women, Hysterectomised women were excluded. Results: 72% of the clients had awareness of contraception. Most common method known is Female sterilization followed by IUCD. Awareness of emergency contraception was found only in 5.33%. 48% of the clients did not follow any method of contraception. Most commonly used method is female sterilization. Conclusions: The study shows that we need to use multiple resources to educate people by intensifying IEC activities. Women should be made aware about their right of protecting their own health and more emphasize should be given on postpartum family planning.